2007
DOI: 10.1186/1745-6215-8-41
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment of young women to a trial of chlamydia screening – as easy as it sounds?

Abstract: Background: Recruiting to trials is complex and difficult. The Prevention of Pelvic Infection (POPI) trial aims to see if screening women for chlamydia and treating those found to be infected reduces the incidence of pelvic inflammatory disease in the following twelve months. It focuses on young, sexually active, multiethnic, mainly inner city, female students. The main aim of this paper is to describe our recruitment methods. Secondary aims in two small subgroups, are to compare characteristics of women recru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 7 publications
0
18
0
Order By: Relevance
“…The design and recruitment methods of the Prevention of Pelvic Infection (POPI) chlamydia screening trial have been described elsewhere [21,22]. Briefly, 2529 female students were recruited from 20 London universities and further education colleges.…”
Section: Methodsmentioning
confidence: 99%
“…The design and recruitment methods of the Prevention of Pelvic Infection (POPI) chlamydia screening trial have been described elsewhere [21,22]. Briefly, 2529 female students were recruited from 20 London universities and further education colleges.…”
Section: Methodsmentioning
confidence: 99%
“…Recent research has focused on strategies of how recruitment can be improved in different settings of clinical research [17-19] and systematic reviews on the topic have identified several interventions, e.g. increasing awareness of the health problem being studied, monetary incentives, using an ‘open label’ rather than placebo design, or making trial materials culturally sensitive [20-22].…”
Section: Introductionmentioning
confidence: 99%
“…2 At baseline, participants completed questionnaires on demographic characteristics, sexual behaviour and history of sexually transmitted infections (STIs). They then provided selftaken vaginal swabs, which were stored in Aptima transport medium (Gen-Probe Inc.,).…”
mentioning
confidence: 99%